Granular Cell Tumour in a California Kingsnake (Lampropeltis californiae). (February 2020) - Reifinger, M.; Dinhopl, N.; Gumpenberger, M.; Konecny, M.; Cigler, P.
Summary: A 21-year-old female California kingsnake ( Lampropeltis californiae ) was presented to the University of Veterinary Medicine, Vienna, Austria, with a space-occupying mass in the caudal abdomen. Following clinical, radiological and sonographical evaluation the mass was removed surgically. Histopathology and transmission electron microscopy confirmed the diagnosis of a granular cell tumour, but immunohistochemical labelling for a range of markers was negative. This lesion is rare in mammals and birds, but has not been reported previously in a reptile.